Detection of Lupus-Like Anticoagulants by an Enzyme-Linked Immunosorbent Assay Using a Partial Thromboplastin as Antigen; A Comparative Study - Arnout, J; Huybrechts, E; Vanrusselt, M; Falcon, C; Vermylen, J (Thrombosis and Haemostasis, 1990)
Clotting assays allow qualitative rather than quantitative detection of the lupus anticoagulant. We have therefore studied the usefulness of an ELISA using a commercial partial thromboplastin, Thrombofax, oS antigen; the results obtained on 146 selected patient plasmas were compared to the results of coagulation tests (kaolin clotting time, tissue thromboplastin inhibition test, activated partial thromboplastin time) and of ELISAs using cardiolipin or phosphatidylserine as antigen. While satisfactory agreement was found within the group of coagulation tests or that of ELISAs, only a moderate agreement was obtained between clotting tests and ELISAs, the best being with the partial thromboplastin ELISA using low plasma dilutions. The study further indicates that ELISA techniques cannot entirely replace coagulation tests for the detection of a lupus anticoagulant, even when a partial thromboplastin is used as antigen. On the other hand, coagulation tests are less sensitive than ELISAs for the detection of antiphospholipid antibodies.